An evaluation of farmer field school induced changes in Ghanaian cocoa production - Gockowski, J.; Asamoah, C.; David, S.; Gyamfi, I.; Adu-Kumi, M. (Journal of International Agricultural and Extension Education, 2010)
A case study of Ghanaian cocoa farmer field schools was conducted to provide feedback on a regional effort to close the yield gap across the cocoa belt of West Africa. Production practices were significantly modified in the year following training with notable increases registered in both the number of producers planting hand pollinated hybrid cocoa seedlings and in the area planted to hybrids. The effectiveness of pesticide application on farms of trained participants was significantly higher following training. Nearly 30 percent of the trained farmers were women, who appeared to derive a lower benefit from training as compared to men, although the result was on the borderline of statistical significance. In sum, farmer field school training and subsequent changes in management practices are estimated to have resulted in a net production increase of 14% for the average farmer field school participant. To improve the impact for women more attention should be given to their specific needs. Expansion of the curriculum to cover nursery management and planting/replanting options should also be considered.